Features of rheological model of the vibrated concrete mix and it influence on durability - Губа, Виктория Викторовна; Герасименко, Виталий Григорьевич; Мастепан, Андрей Николаевич; Городничий, Александр Владимирович; Кротов, Роман Викторович (Eastern-European Journal of Enterprise Technologies, 2010)
Questions of influence of shift and normal vibrations, at a stage of consolidation of a concrete mix are considered, at imposing concerning weak vibrations. At vibrating, resistance to shift disappears. The given model of a vibrated concrete mix gets new quality.